1972
DOI: 10.1515/zna-1972-1208
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Quenching and Depolarisation of Photoluminescence in Solutions

Abstract: The emission anisotropy r/r0 and quantum yield rjlrj0 of the photoluminescence of glycerin-water solutions of Na-fluorescein has been measured at concentrations 10 -6 -3-10 -1 M. The drop of r/lr]0 is connected with a repolarisation effect, which is interpreted by a completed theory of concentrational depolarisation of photoluminescence (CDPL), accounting the self-quenching by nonluminescent dimers and the remigration of excitation energy. The dimerisation constant and the critical concentrations have been det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

1979
1979
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 3 publications
1
0
0
1
Order By: Relevance
“…As was shown in many papers, Jablonski's theory of concentrational quenching of luminescence [11,12,29,36,[37][38][39][40] and its generalisation by Kawski [22,41,42] and Bojarski [43,44] is in good agreement with experiment. In the present paper it is shown that Jablonski's model of a luminescence centrum acquires a new meaning as a real physical object of well defined physico-chemical properties in micellar solutions.…”
Section: Methodssupporting
confidence: 65%
“…As was shown in many papers, Jablonski's theory of concentrational quenching of luminescence [11,12,29,36,[37][38][39][40] and its generalisation by Kawski [22,41,42] and Bojarski [43,44] is in good agreement with experiment. In the present paper it is shown that Jablonski's model of a luminescence centrum acquires a new meaning as a real physical object of well defined physico-chemical properties in micellar solutions.…”
Section: Methodssupporting
confidence: 65%
“…Das führt außerdem zu einer Repolarisation [2,6], die von Bojarski mehrfach diskutiert wurde [8][9][10][11][12].…”
unclassified